Steady Flow over a Rotating Disk in Porous Medium with Heat Transfer - Attia, H. A. A. (Nonlinear Analysis: Modelling and Control, 2009)
The steady flow of an incompressible viscous fluid above an infinite rotating disk in a porous medium is studied with heat transfer. Numerical solutions of the nonlinear governing equations which govern the hydrodynamics and energy transfer are obtained. The effect of the porosity of the medium on the velocity and temperature distributions is considered.
Keywords: rotating disk; porous medium; heat transfer; numerical solution